The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/gbe/evu123
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Genome Flux and Its Role in the Differentiation of Bacterial Lineages

Abstract: Horizontal gene transfer (HGT) and gene loss are key processes in bacterial evolution. However, the role of gene gain and loss in the emergence and maintenance of ecologically differentiated bacterial populations remains an open question. Here, we use whole-genome sequence data to quantify gene gain and loss for 27 lineages of the plant-associated bacterium Pseudomonas syringae. We apply an extensive error-control procedure that accounts for errors in draft genome data and greatly improves the accuracy of patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 86 publications
5
82
2
Order By: Relevance
“…In most studies this is apparent from a decrease in the rate of gene content change relative to the rate of nucleotide substitution in the deeper branches of the phylogeny compared to the tips. The same pattern is most elegantly demonstrated in the P. syringae and E. coli studies [21,22] in which the vast majority of individual gene gains are mapped to a single strain. There are three potential explanations for why most gene content changes are transient.…”
Section: Quantifying the Rate And Fate Of Changes In Gene Contentmentioning
confidence: 55%
See 1 more Smart Citation
“…In most studies this is apparent from a decrease in the rate of gene content change relative to the rate of nucleotide substitution in the deeper branches of the phylogeny compared to the tips. The same pattern is most elegantly demonstrated in the P. syringae and E. coli studies [21,22] in which the vast majority of individual gene gains are mapped to a single strain. There are three potential explanations for why most gene content changes are transient.…”
Section: Quantifying the Rate And Fate Of Changes In Gene Contentmentioning
confidence: 55%
“…Similar estimates were found in Streptococcus [19] and Corynebacterium [20] genomes using the same methodology. A recent estimate of LGT rate in Pseudomonas syringae based on stochastic mapping methodology (after corrections necessary for working with genomes that are not sequenced to complete closure) was found to be four orders of magnitude higher than the estimate for B. cereus [21]. Individual P. syringae lineages could be shown to have acquired thousands of genes in the same period in which a 1% amino acid divergence accrued in the core genome.…”
Section: Quantifying the Rate And Fate Of Changes In Gene Contentmentioning
confidence: 90%
“…[49] In addition, genes that are gained seem to be labile through evolutionary time, and are readily lost, while mutations tracing vertical phylogenetic signal continue to accumulate in the core genome. [50] Recent analyses of HGT across genomes suggest that long term successful transfer of genes across lineages is rare, [49] leaving phylogenetic structure intact. [51] These results are consistent with the observation that bacteria do form biologically coherent groups, which would not be expected if horizontal gene flow were rampant and unconstrained.…”
Section: A Tree Of Life Model Is Usefulmentioning
confidence: 99%
“…Likewise, it has been shown that new gene copies arise more often through LGT than through duplication (Treangen & Rocha 2011), and population genomic studies have revealed that isolates with nearly 5 identical nucleotide composition in the genes they share can differ by many hundreds of accessory genes (e.g. (Nowell et al 2014)), indicating that LGT might be more important than mutation. Indeed, over large evolutionary timescales LGT events can completely transform the genomic make-up, metabolism and ecological life-styles of bacterial lineages (e.g.…”
Section: Genomic Change 'From Without': Incorporating Foreign Dnamentioning
confidence: 99%